Analisis Faktor Penyebab Kemiskinan dan Bagaimana Penanggulangannya : Studi Empiris Pada 29 Kabupaten di Jawa Tengah 2014-2020 - Dicki Dwi Ferian; Edy Yusuf Agung Gunanto (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Community welfare is an indicator of the success of development. And in its implementation, economic development will be faced with various problems related to the welfare of society. One of the complex and chronic problems related to the welfare of the community is poverty. The high of poverty rate will have an impact on the emergence of other negative social problems. It is difficult to find out what the exact cause is and how the solution is really effective in reducing the poverty. In this regard, the problem of poverty in Central Java is related to its slow pace of poverty reduction and the high level of poverty in Central Java which is always above the national level. The aim of this research is to see how the factors that cause poverty and how to eradicate it based on theories and related previous research. Unemployment, dependency ratio, and productivity variables were analyzed as factors causing poverty. while agrishare, industrialshare, and village funds were analyzed as factors that were considered capable of eradicating poverty. The analytical tool used is multiple linear regression with panel data and estimated using the fixed effect model approach with pooled generalized least square estimate with cross section weight. The results showed that the variables of agrishare, industrialshare, labor productivity, and village funds had a significant effect on poverty. While the unemployment variable and dependency ratio do not have a significant effect on poverty.